Powrót do przestępstwa jako "okoliczność obciążająca" - Janiszewski, Bogusław (Wydział Prawa i Administracji UAM, 1993)
One of t h e circumstances taken into account in deciding on the measure of penalty is "the past behaviour" of an offender. However, as long as one does not specify what, in such a context, is the object of condemnation (disapproval) connected with the measure of penalty, one will be unable to reach a necessary degree of clarity in evaluating this circumstance. The object of such condemnation is an offensive act, and return to crime has no influence, with few exceptions, on the evaluation of such an act from the point of view of the measure of penalty. Return to crime is here merely a prognostic factor, and is treated purely "technically". It may serve the preventive aims of the measure of penalty, within the limits determined by the commensurability of penalty to the degree of guilt.
Return to crime as an aggravating circumstance